2014
DOI: 10.1017/s0317167100017248
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Cognitive Decline in Transient Ischemic Attack Patients

Abstract: Stroke is the leading cause of prolonged disability in the elderly and the second most common cause of death. 1,2 prior to stroke individuals often experience minor cerebrovascular events such as transient ischemic attacks (tias). according to the World health organization criteria, a tia is defined as a focal neurological deficit lasting for less than 24 hours and presumed to be of vascular origin. 3 these events have been considered crucial "warning signs" for increased risk of an upcoming stroke. Stroke has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Mild cognitive impairment was present in a significant portion of this sample with TIA. Cognitive decline can occur due to different causes, such as vascular risk factors and biological aging, and these characteristics are common among patients with TIA diagnosis . Cognitive decline is a strong predictor for TIA/stroke , and cognitive impairment may have occurred before the TIA event for some of the participants in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Mild cognitive impairment was present in a significant portion of this sample with TIA. Cognitive decline can occur due to different causes, such as vascular risk factors and biological aging, and these characteristics are common among patients with TIA diagnosis . Cognitive decline is a strong predictor for TIA/stroke , and cognitive impairment may have occurred before the TIA event for some of the participants in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Large cohort studies have demonstrated that TIA confers substantial short-and long-term risks of stroke, vascular events, myocardial infarction, cognitive impairment, and even death (Touzé et al, 2005;Giles and Rothwell, 2007;Sivakumar et al, 2014). Thus, TIA is a 'warning' event that provides an opportunity for prevention, and new guidelines highlight the need for urgent assessment of those patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the risk of stroke within 90 days after TIA is 10–20%, of which 50% occur within the first 2 days ( Hill et al, 2004 ; Johnston et al, 2007 ). In addition, patients with TIA may experience brain atrophy and cognitive decline, which is a key risk factor for dementia ( Sivakumar et al, 2014 ; van Rooij et al, 2014 ; Bivard et al, 2018 ). However, the pathogenesis and pathophysiological changes associated with TIA have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%